OPTICAL AND ELECTROPHYSICAL PROPERTIES OF ZnO FILMS INTRODUCED WITH Al ATOMS HEAT PROCESSED AT DIFFERENT TEMPERATURES (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
Aluminum oxide (AZO) thin films were deposited on glass substrates using the sol-gel dip coating method. The effect of temperature on electrical and optical conductivity properties of Al-doped ZnO thin films was studied. The ratio of the mass of Al atoms to the mass of Zn atoms was chosen to be 3%. ZnO films with Al atoms heat treated at 550℃ showed high transmittance up to 84% in the visible and near-infrared radiation fields. When Al atoms are introduced, it is found that the main charge carriers are n types.